Phonology of Savu Language Mehara Dialect: Descriptive Generative - Rudolof J. Isu; Rocky P. Sekoni; Temy M.E. Ingunau (Universitas Nahdlatul Wathan Mataram, 2023)
Savu language, Mehara dialect is the language of the Savu indigenous people located in Savu island, Savu Raijua district, East Nusa Tengggara province. This paper only focuses on the Mehara dialect of Savu language. The purpose of this research is to reveal the sound process or phonology of Savu language in Mehara dialect. In this article, the theory used is the Generative phonology approach with qualitative methods. The result of this paper is that Savu language Mehara dialect has 25 phonemes consisting of 6 vowel phonemes and 19 consonant phonemes. Each of these phonemes is a phoneme of origin that can form base morphemes phonetically. (1) Mehara dialect of Savu language has 11 syllable structures. (2). Mehara dialect has 2 phonological processes, namely the process of deletion, and the process of adding glottal [ ' ]. (3). Mehara Savu dialect is a vocalic language because there are no consonants at the end of words. (4). Another prominent feature of Mehara dialect is the sound segments: bilabial aspirate /bh/, dental aspirate /dh/, palatal aspirate /dj/, and velar aspirate /gh/